2009
DOI: 10.1074/mcp.m800238-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Quantitation of Prostate-specific Antigen Biomarker in the Low Nanogram/Milliliter Range by Conventional Bore Liquid Chromatography-Tandem Mass Spectrometry (Multiple Reaction Monitoring) Coupling and Correlation with ELISA Tests

Abstract: Geneviè ve Choquet-Kastylevsky ‡, and Jé rô me Lemoine §ʈProteomics discovery leads to a list of potential protein biomarkers that have to be subsequently verified and validated with a statistically viable number of patients. Although the most sensitive, the development of an ELISA test is time-consuming when antibodies are not available and need to be conceived. Mass spectrometry analysis driven in quantitative multiple reaction monitoring mode is now appearing as a promising alternative to quantify proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 22 publications
(10 reference statements)
4
138
1
2
Order By: Relevance
“…proteins in both single (33)(34)(35)(36)(37)(38)(39)(40) and multiplexed assay formats (41)(42)(43)(44). The proteins quantified in these studies are summarized in Table 1.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…proteins in both single (33)(34)(35)(36)(37)(38)(39)(40) and multiplexed assay formats (41)(42)(43)(44). The proteins quantified in these studies are summarized in Table 1.…”
Section: Reviewsmentioning
confidence: 99%
“…In general, direct plasma or serum digests without prior attempts to minimize sample complexity have resulted in low milligram per liter quantification ranges at best (33,43,45 ). For instance, a number of different studies that have quantified prostate-specific antigen (PSA) through coupling of various sample purification strategies have generally shown that quantification improves from the low milligram per liter range in untreated plasma analysis (33 ) to the low microgram per liter range with prior depletion and fractionation (39,41 ) and the low to sub-microgram per liter range with prior immunoextration (46 ) ( Table 2). Although various confounding factors such as variations in instrumentation used in the different laboratories undoubtedly contributed to some of the differences observed, this trend can also be seen within the same study (Table 2) (41,46 ).…”
Section: Reviewsmentioning
confidence: 99%
“…Keshishian and coworkers developed multiplexed assays for six plasma proteins present in 1–10 ng/ml using strong cation exchange chromatography and major abundant protein depletion, but without immunoaffininty enrichment, demonstrating that the abundance range of typical candidate biomarkers (ng/ml) is achievable with targeted proteomics 82. Fortin and coworkers also achieved ng/ml sensitivity without immunoaffinity enrichment by quantitating prostate‐specific antigen (PSA) in sera from patients with prostate cancer or benign hyperplasia; moreover, their MS results agreed with established ELISA tests for PSA 83. Shi and coworkers used an antibody‐free approach termed PRISM (high‐pressure, high‐resolution separations coupled with intelligent selection and multiplexing) in order to quantitate PSA levels in the range of 50–100 pg/ml, also with excellent correlation to clinical immunoassays 84.…”
Section: Clinical Applicationsmentioning
confidence: 93%
“…The LC-ESI-QqQ in selected or multiple reactions way has been used for routine detection of small molecules including metabolites and drugs [31] . More recently, the LC-ESI-QqQ has been suggested as a replacement for classical ELISAs for the quantitation of proteins in complex matrices [98] . The MALDI triple quadruple measures enzyme-mediated, time-dependent hydrolysis of the β -lactam ring structure of penicillin G and ampicillin and inhibition of hydrolysis by clavulanic acid for clavulanic acid susceptible β -lactamases.…”
Section: Other Technologiesmentioning
confidence: 99%